2018
DOI: 10.1093/infdis/jiy056
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Syncytial Virus Seasonality: A Global Overview

Abstract: Respiratory syncytial virus (RSV) is the leading cause of acute lower respiratory infections in children. By the age of 1 year, 60%-70% of children have been infected by RSV. In addition, early-life RSV infection is associated with the development of recurrent wheezing and asthma in infancy and childhood. The need for precise epidemiologic data regarding RSV as a worldwide pathogen has been growing steadily as novel RSV therapeutics are reaching the final stages of development. To optimize the prevention, diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
226
3
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(284 citation statements)
references
References 35 publications
23
226
3
5
Order By: Relevance
“…It is clear that our approach, using mostly routine diagnostic test data, has some disadvantages, as it is not based on systematic sentinel surveillance, unlike the routine influenza surveillance in many countries. However, our findings, based mostly on routinely collected diagnostic data for influenza and RSV, are similar to those reported by other global studies using mainly national surveillance data, [31][32][33][34] i.e. that there are annual seasonal peaks of influenza and RSV in the colder months in the Northern and Southern hemispheres, with more year-round activity in the subtropical/tropical regions.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It is clear that our approach, using mostly routine diagnostic test data, has some disadvantages, as it is not based on systematic sentinel surveillance, unlike the routine influenza surveillance in many countries. However, our findings, based mostly on routinely collected diagnostic data for influenza and RSV, are similar to those reported by other global studies using mainly national surveillance data, [31][32][33][34] i.e. that there are annual seasonal peaks of influenza and RSV in the colder months in the Northern and Southern hemispheres, with more year-round activity in the subtropical/tropical regions.…”
Section: Discussionsupporting
confidence: 90%
“…over the same time period) incidence patterns of common respiratory viruses across different countries -and nearly all of these used mostly publicly available surveillance data extracted from national surveillance websites, or published studies. [31][32][33][34][35] However, it is clear from the literature that international collaborations are increasing, in an effort to pool and compare such contemporaneous epidemiological data, to improve our understanding of how these respiratory viruses are behaving -not just within our local or national populations, but simultaneously across the world. Although national surveillance data are invaluable to reveal how these viruses are behaving and moving through populations, and also capture the incidence of viral infections in the community to some extent, the bulk of that population's healthcare burden may be more accurately represented by the routine diagnostic testing data obtained from patients who were sufficiently ill to be admitted to hospital.…”
Section: Introductionmentioning
confidence: 99%
“…It was surprising that in this study, RSV was detected simultaneously for only a year within the two-year study period of children hospitalized with pneumonia. However, peak was observed in winter during December to February, which was similar to what some other countries reported in a recent review article on RSV seasonality [54]. The review article reported that, epidemic in different countries were consistent between different years with some changes between seasons observed from year to year.…”
Section: Discussionsupporting
confidence: 87%
“…RSV is a paramyxovirus in the genus pneumovirus that causes sea sonal annual epidemics worldwide; yearround disease is seen in some tropical locations. 60 Risk factors for more severe disease after organ transplantation in clude lung transplantation, infection in children under a year of age or with underlying lung disease. 61 Early acquisition of RSV after trans plantation or after augmented immunosuppression has been associ ated with increased severity of disease in some but not all studies.…”
Section: Virology and Epidemiologymentioning
confidence: 99%